Role Of Low Dose Aspirin In Preventing Preterm Birth In Patients With Previous History Of Preterm Delivery - Sadaf, Maliha; Saleem, Aasia; Farkhanda, Tallat; Iqbal, Khansa; Ashraf, Sabeen; Iftikhar, Amna (Journal of Rawalpindi Medical College, 2023)
Objective: Preterm birth (PTB) occurs between 24-37 weeks of gestation. The important risk factor for PTB is a previous PTB and currently progesterone is used for the management of recurrent spontaneous PTB. Some studies have shown good outcomes but recent studies revealed that the use of vaginal progesterone was not related to a decreased likelihood of PTB or neonatal adverse effects. Thus, the controversy in the literature suggests multiple underlying pathological mechanisms involved in the progression of PTB. This study aims to determine the role of low-dose aspirin in the prevention of preterm birth in patients with a previous history of preterm delivery. Methodology: In this randomized controlled trial, a total of 172 patients fulfilling the inclusion criteria were selected from the inpatient and outpatient departments. Patients were divided randomly into two groups (group A and group B), using random number tables. In Group A, low-dose aspirin (75mg) was given while group B was taken as a control group. Patients were called every 8 weeks in the outpatient department for the assessment of compliance and side effects of the drug. The data were entered and analyzed by using SPSS v25.0. Chi-square was used to compare the two groups for incidence of preterm birth. Relative risk (along with a 95% confidence interval) for the decrease in the incidence of preterm birth with the use of aspirin was calculated. Results: The age of participants included in the study was 18 to 40 years. The mean age of patients in group A was 33.85±5.210 years and in group B was 32.86±4.139 years. The mean fetal birth weight in group A was 2281.1962±363.125 grams and in group B was 2271.4344±374.797 grams. In the low-dose aspirin group, 10(11.6%) had preterm birth and 31(36.0%) in the control group with a p-value of 0.001, which is statistically significant. The risk of having preterm birth with low-dose aspirin was 1.801 times less than controls. Conclusion: aspirin in low dose given before 14 weeks of gestation decrease spontaneous preterm birth as compared to the control group in a woman with a history of previous preterm birth which was spontaneous